Rash with DERMABOND PRINEO Skin Closure System Use in Bilateral Reduction Mammoplasty: A Case Series - R. W. Knackstedt; J. A. Dixon; P. J. O’Neill; F. A. Herrera (Case Reports in Medicine)
Background. Bilateral reduction mammoplasty is a common plastic surgery procedure that can be complicated by unfavorable scar formation along incision sites. Surgical adhesives can be utilized as an alternative or as an adjunct to conventional suture closures to help achieve good wound tension and provide an adequate barrier with excellent cosmesis. The recently introduced DERMABOND PRINEO Skin Closure System Skin Closure System combines the skin adhesive 2-octyl cyanoacrylate with a self-adhering polyester-based mesh. Proposed benefits of wound closure with DERMABOND PRINEO Skin Closure System, used with or without sutures, include its watertight seal, easy removal, microbial barrier, even distribution of tension, and reduction in wound closure time. Although allergic reactions to 2-octyl cyanoacrylate have been reported, few allergic reactions to DERMABOND PRINEO Skin Closure System have been noted in the literature. This case series describes three patients who experienced an allergic reaction to DERMABOND PRINEO Skin Closure System after undergoing elective bilateral reduction mammoplasties at our institution to further explore this topic. Methods. Retrospective chart review of bilateral reduction mammoplasty patients who received DERMABOND PRINEO Skin Closure System dressing at our institution was performed. Results. Three patients were identified as having a rash in reaction to DERMABOND PRINEO Skin Closure System after bilateral reduction mammoplasty. All three patients required systemic steroid treatment to resolve the rash. One patient was identified as having a prior adhesive reaction. Conclusions. DERMABOND PRINEO Skin Closure System has demonstrated its efficacy in optimizing scar healing and appearance. However, as we demonstrate these three allergic reactions to DERMABOND PRINEO Skin Closure System, caution must be utilized in its usage, namely, in patients with a prior adhesive allergy and in sites where moisture or friction may be apparent.